Advances in Human Factors in Wearable Technologies and Game Design Proceedings of the AHFE 2018 International Conferences on Human Factors and Wearable Technologies, and Human Factors in Game Design and Virtual Environments, Held on July 21-25, 2018, in Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Ahram, Tareq Z. (Advances in Intelligent Systems and Computing, 2019)
This book focuses on the human aspects of wearable technologies and game design, which are often neglected. It shows how user centered practices can optimize wearable experience, thus improving user acceptance, satisfaction and engagement towards novel wearable gadgets. It describes both research and best practices in the applications of human factors and ergonomics to sensors, wearable technologies and game design innovations, as well as results obtained upon integration of the wearability principles identified by various researchers for aesthetics, affordance, comfort, contextual-awareness, customization, ease of use, ergonomy, intuitiveness, obtrusiveness, information overload, privacy, reliability, responsiveness, satisfaction, subtlety, user friendliness and wearability. The book is based on the AHFE 2018 Conference on Human Factors and Wearable Technologies and the AHFE 2018 Conference on Human Factors in Game Design and Virtual Environments , held on July 21-25, 2018 in Orlando, Florida, and addresses professionals, researchers, and students dealing with the human aspects of wearable, smart and/or interactive technologies and game design research.